Kindergartens in the era of digitization: a forward-looking vision - Bennya, Ahlam; Yala, Farouk (Journal of Human Sciences, 2021)
This research paper tries to present a modern vision for teaching and learning in the information age through anticipating the digitization of kindergartens and transforming them from stereotypical to informatics, by moving from traditional educational programs, methods and boring teaching methods that depend on memorization and indoctrination to modern methods and techniques in an attractive scientific template that depends on understanding and thinking skills.This is achieved by integrating the computer into its programs as a strategic choice. Scientific studies have proven its effectiveness in sharpening the talents of the child and exploding his energies in a creative, unconventional way that depends mainly on computerized programs designed on scientific foundations under the supervision of an academically and professionally qualified educator working to raise the level of educational outcomes in line with the specifications of a kindergarten Tomorrow that will qualify her children for professions we do not know yet; As the world of tomorrow is the world of digitization, or rather the world of inventions in various areas of life.